Fenomena Laki-Laki Feminim sebagai Tren Baru dalam Strategi Pemasaran Produk Kecantikan - Budi Arif Suyanto; Annafi, Muhammad Hafiyyan (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
The phenomenon of masculine men has become a new strategy in the modern beauty product marketing industry. Changing social and cultural values about gender identity have led to the emergence of male images with soft, stylish, and aesthetic characteristics in various promotional campaigns. This study aims to analyze how the phenomenon of masculine men is used as a marketing communication strategy, as well as its impact on consumer perception. The method used is a literature study with a descriptive qualitative approach, which examines contemporary communication theory, gender theory, and modern marketing concepts. The findings suggest that the use of masculine male figures in beauty product advertising can expand market segmentation, attract cross-gender audiences, and create an inclusive brand image that aligns with current social trends. However, this strategy also raises debates about the limitations of masculinity and the social construction of beauty. Therefore, the phenomenon of masculine men can be understood as a form of adaptation of marketing communication to changes in cultural and gender values in contemporary society In addition, the findings of this study are expected to make a theoretical contribution to the study of marketing communication and gender studies, as well as become a practical reference for beauty industry players in designing promotional strategies that are sensitive to social dynamics, cultural values, and the increasingly diverse preferences of modern consumers.